Effects of hydrotreated vegetable oil on emissions of aerosols and gases from light-duty and medium-duty older technology engines - Bugarski, Aleksandar D.; Hummer, Jon A.; Vanderslice, Shawn (Journal of occupational and environmental hygiene, 2016)
This study was conducted to assess the potential of hydrotreated vegetable oil renewable diesel (HVORD) as a control strategy to reduce exposure of workers to diesel aerosols and gases. The effects of HVORD on criteria aerosol and gaseous emissions were compared with those of ultralow sulfur diesel (ULSD). The results of comprehensive testing at four steady-state conditions and one transient cycle were used to characterize the aerosol and gaseous emissions from two older technology engines: (1) a naturally aspirated mechanically controlled and (2) a turbocharged electronically controlled engine. Both engines were equipped with diesel oxidation catalytic converters (DOCs). For all test conditions, both engines emitted measurably lower total mass concentrations of diesel aerosols, total carbon, and elemental carbon when HVORD was used in place of ULSD. For all test conditions, the reductions in total mass concentrations were more substantial for the naturally aspirated than for the turbocharged engine. In the case of the naturally aspirated engine, HVORD also favorably affected total surface area of aerosols deposited in the alveolar region of human lungs (TSAADAR) and the total number concentrations of aerosols. In the case of the turbocharged electronically controlled engine, for some of the test conditions HVORD adversely affected the TSAADAR and total number concentrations of aerosols. In the majority of the test cases involving the naturally aspirated mechanically controlled engine, HVORD favorably affected carbon dioxide (CO 2 ), nitrogen oxides (NO X ), and nitric oxide (NO) concentrations, but adversely affected NO 2 and total hydrocarbon concentrations, while the effects of the fuels on carbon monoxide (CO) concentrations were masked by the effects of DOC. In the case of the turbocharged electronically controlled engine, the CO 2 , CO, NO X , NO, and total hydrocarbon concentrations were generally lower when HVORD was used in place of ULSD. The effects of the fuels on NO 2 concentrations were masked by the more prominent effects of DOC.